The Jesuit relations and allied documents: travels and explorations of the Jesuit missionaries in New France, 1610-1791 ; the original French, Latin, and Italian texts, with English translations and notes - Thwaites, Reuben Gold (Burrows Bros. Co., 1896)
Acadia: v. 1. 1610-1613 -- v. 2. 1612-1614 -- v. 3. 1611-1616 -- v. 4. Acadia and Quebec, 1616-1629 -- Quebec: v. 5. 1632-1633 --v. 6. 1633-1634 -- Quebec, Hurons, Cape Breton: v. 7. 1634-1635 -- v. 8. 1634-1636 -- v. 9. Quebec, 1636 -- v. 10. Hurons, 1636.